Ultrasmall silicon nanoparticles as a promising platform for multimodal imaging. (28th February 2020) - Singh, Garima; Ddungu, John L. Z.; Licciardello, Nadia; Bergmann, Ralf; De Cola, Luisa; Stephan, Holger
Abstract : Biocompatible ultrasmall silicon nanoparticles (2.4 ± 0.5 nm) equipped with both a near-infrared dye and a radiolabel provide reliable information about biodistribution and pharmacokinetic properties. Abstract : Bimodal systems for nuclear and optical imaging are currently being intensively investigated due to their comparable detection sensitivity and the complementary information they provide. In this perspective, we have implemented both modalities on biocompatible ultrasmall silicon nanoparticles (Si NPs). Such nanoparticles are particularly interesting since they are highly biocompatible, have covalent surface functionalization and demonstrate very fast body clearance. We prepared monodisperse citrate-stabilized Si NPs (2.4 ± 0.5 nm) with more than 40 accessible terminal amino groups per particle and, for the first time, simultaneously, a near-infrared dye (IR800-CW) and a radiolabel ( 64 Cu-NOTA = 1, 4, 7-triazacyclononane-1, 4, 7-triacetic acid) have been covalently linked to the surface of such Si NPs. The obtained nanomaterials have been fully characterized using HR-TEM, XPS, UV-Vis and FT-IR spectroscopy. These dual-labelled particles do not exhibit any cytotoxicity in vitro . In vivo studies employing both positron emission tomography (PET) and optical imaging (OI) techniques revealed rapid renal clearance of dual-labelled Si NPs from mice.